Secure and efficient pseudonymization for privacy-preserving vehicular communications in smart cities. (March 2020) - Bouchelaghem, Siham; Omar, Mawloud
Highlights: This work introduces an efficient pseudonym changing strategy in vehicular networks. Cryptographic primitives and vehicular communications are combined to ensure location privacy. Well-known security and privacy threats are prevented at low computational cost. Proposed approach achieves better performances compared to existing solutions of the literature. Simulation results show suitability of the proposed approach for ITS applications. Abstract: The emergence of modern Intelligent Transportation Systems (ITS) based on vehicular networks (VNs) has diversified the range of applications provided to drivers and passengers during their road trips. To fully benefit from these services, vehicles need however to share their geolocation data making location privacy a critical issue. Hence, to mitigate these threats and promote VNs use in developing Smart Cities, it is vital to guarantee conditional anonymity to vehicular users. In this paper, we propose an efficient pseudonym changing strategy for privacy-preserving in VNs. The proposed approach uses threshold cryptography properties to provide moving vehicles with pseudonyms, allowing them to communicate anonymously during their journey. These vehicles though can be traced back by trusted authorities in case of misbehavior actions. We evaluate the efficiency of the proposed approach by comparison with concurrent solutions, where it demonstrates the best results in both congested road traffic and dense infrastructure deployment scenarios.